Lifestyle Patterns Among People Living With HIV in Peer Support Groups: Socioeconomic and Clinical Predictors of Health-Promoting Behaviors - Sri Handayani; Susana Nurtanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
As HIV transitions into a manageable chronic condition, optimizing lifestyle behaviors is key to achieving long-term health outcomes. This study aims to explore lifestyle behaviors in people with HIV (ODHIV) who participate in peer support groups as well as identify socioeconomic and clinical predictors of healthy lifestyle engagement. The research design was a cross-cutting analysis involving 250 ODHIV registered in a community support group. Lifestyle behavior was measured using a modified Health-Promoting Lifestyle Profile II (HPLP-II) instrument. Multivariate logistic regression analysis was used to determine independent predictors, with Nagelkerke R² and Hosmer–Lemeshow tests to assess model suitability. The results showed that 56.2% of respondents had a healthy lifestyle. Factors of higher education (OR = 2.77; p = 0.006), older age (OR = 2.32; p = 0.015), employment status (OR = 2.00; p = 0.029), and longer duration of ART therapy (OR = 1.17 per year; p = 0.003) were significant predictors. The model explains 32% of lifestyle variations, with ART compliance and substance control as the strongest behavioral domains. These findings confirm the role of peer support groups as a behavioural reinforcement environment, but socioeconomic disparities remain influential. The integration of theory-based lifestyle interventions into community-based HIV services is necessary to optimize chronic disease outcomes.